PENGEMBANGAN MODUL PRAKTIKUM SERLI (DISCOVERY LEARNING) UNTUK PEMBELAJARAN SAINS DI SEKOLAH DASAR - Thalib, Azizah; Winarti, Puji; Sani, Nurul Kami (Universitas Muhammadiyah Surakarta, 2020)
This study aims to develop a Serli Practicum Module (Discovery Learning) for Science learning in Class VI Elementary Schools that has met valid, practical, and effective criteria for use in Science learning in elementary schools. This type of research is research and development that uses the Peffers et al development model. The type of development research includes six phases, namely: (1) identifying problems that motivate research, (2) describing research objectives, (3) designing and developing products, (4) testing products, (5) evaluating trial results, and (6) ) communicating results. The results of the study show that the Serli Practicum Module (Discovery Learning) for Science learning in Class VI Elementary School has been valid, practical and effective. Validity values obtained are 61 with very valid criteria. Practical value of 65.73 or very practical. And the acquisition of effectiveness value is 0.70 with effective criteria.